Development of a Learning Management System Using Moodle in the Arabic Language Education Study Program / Pengembangan Learning Management System menggunakan Moodle pada Program Studi Pendidikan Bahasa Arab - Muhammad Zaky Sya'bani; Khairil Anwar (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
This research is motivated by the demands of the times in the world of education which require managers of educational institutions and stakeholders to be able to improve digital literacy skills. The Covid 19 pandemic situation makes learning to switch to learning in a structured network. This study aims to develop the Moodle Learning Management System in PBA Study Program and see the effectiveness of using the Moodle LMS. This research uses the R&D research method with the Borg and Gall development model. The results of this study are (1) The development of the Moodle LMS in this study uses the Borg and Gall development model. The courses that the researchers developed were fahmul masmu in PBA study programs. In the validity process of the Moodle LMS that was developed, the researcher presented 3 experts, namely: media, material and language experts. As for the results of the validity questionnaire, it was analyzed with Aiken validity which obtained a value of 0.88 with valid information for material, 0.89 with valid information for media and a value of 0.88 with valid information for language. (2) The effectiveness of using LMS Moodle in learning Arabic reaches 82.64% with the statement "effective". So it can be concluded that the development of Moodle LMS is effective in supporting Arabic learning.المستخلص: خلفية هذا البحث هو متطلبات العصر في عالم التعليم والتي تتطلب من مديري المؤسسات التعليمية وأصحاب المصلحة أن يكونوا قادرين على تحسين مهارات القراءة والكتابة الرقمية. و إن الوضع الوبائي لـكوفيد Covid 19 يجعل التعلم يتحول إلى التعلم في شبكة منظمة. تهدف هذا البحث إلى تطوير نظام إدارة التعلم مودل (Moodle) في قسم تعليم اللغة العربية ومعرفة مدى فعالية استخدام نظام إدارة التعلم مودل. يستخدم هذا البحث منهج البحث والتطوير مع نموذج التطوير بورج وجال(Borg & Gall). ونتيجة من هذا البحث هي 1. إنتاج نظام إدارة التعلم مودل. والمقررات التي طورها الباحث هي "فهم مسموع" في قسم تعليم اللغة العربية. وفي عملية التحقق من صحة نظام إدارة التعلم مودل الذي تم تطويره، قدم الباحث 3 خبراء وهم: خبراء الإعلام والمادة واللغة. أما نتائج استبيان الصدق فقد تم تحليلها باستخدام صدق أيكن (Aiken) حيث حصلت على قيمة 0.88 بمعلومات صحيحة للمادة، و0.89 بمعلومات صحيحة للوسائط وقيمة 0.88 بمعلومات صحيحة للغة. 2. فعالية استخدام نظام إدارة التعلم مودل في تعلم اللغة العربية تصل إلى 82.64% بعبارة "فعال". ومن هنا يمكن الاستنتاج أن تطوير نظام إدارة التعلم مودل فعال في دعم تعلم اللغة العربية.